Planning and implementing : Assessment - Freeman, Richard; Lewis, Roger (London : Kogan page, 1998)
This title outlines a set of principles and analytical methods that can be adapted to different assessment scenarios designed to enable readers to construct their own effective methods for assessment. Guidelines for design and methods of planning, choosing and implementation are provided.
Includes bibliographical reference and index.
Keywords: Educational tests and measurements; EDUCATION -- Administration -- General